Building a wireless telemedicine network within a wimax based networking infrastructure - CHorbev, Ivan; Mihajlov, Martin (IEEE, 2009)
In this paper we propose an implementation of a WiMAX-based integrated system for e-medicine in the Republic of Macedonia. We present developed telemedicine multimedia services and their related QoS. We also present the problems and challenges for using a public wireless IP network for setting up the system.